KEBIJAKAN PENGANGGARAN DAERAH DIMASA PANDEMI COVID-19 (STUDY KASUS PADA PEMERINTAH DAERAH PROVINSI BANTEN) - Natta Sanjaya (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2020)
The problem in this research, the Provincial Government of Banten faced on the condition of the regional economy sluggish due to pandemic Covid-19 so it requires a scheme of setting budgetary policy of regions, ranging from setting regional revenue, regional expenditure, up to the setting of local financing. According to the Circular Letter of the Minister of Finance and Minister of internal Affairs, Local Government is obliged to make the mechanism of setting the Budget Revenue and Expenditure through refocusing and reallocation of the budget. The purpose of this study is to determine how the policy of local budgeting in the pandemic Covid-19 study case on Local Government of Banten Province. The method used in this research is descriptive qualitative using Purposive Sampling. The results showed the policy of the management of the regional budget in the pandemic Covid-19 at the Provincial Government of Banten that, the Provincial Government of Banten has been running a budget management in accordance with the directives and policies that have been set by the central government through the mechanism of refocusing and reallocation of the budget revenue, expenditure, and financing the area appropriately.Â